(untitled) (Studia austriaca, 2012)
This essay investigates the constellations of “double” in Meyrink’s novel Der Golem to the extent that the Golem derives its terror not from something alien or unknown but from something strangely familiar, which defeats our efforts to separate ourselves from it. According to this theory, the Golem turns out to be both the product of a psychic dissociation of the main character, due to a comeback of his “removed past” induced by hypnosis, and the Jewish ghetto’s spirit brought to life by the suffering that its inhabitants have endured over the centuries. This essay also focuses on Pernath’s process of initiation, which aims at the conquest of his cultural memory.